Hallyu Di Tiongkok Setelah Kesepakatan Three NOs - Yusminda, Zahara; Yusra, Muhammad; Austin, Diah Anggraini (Palito, 2024)
On 2016, diplomatic relations between South Korea and Tiongkok deteriorated because THAAD. During the THAAD crisis,Tiongkok banned all activities related to the hallyu. Moon Jae In offering Three Nos agreement to Tiongkok try to improve diplomatic relations. This research aims to describe and analyze South Korea’s effort in dissemination the Hallyu in Tiongkok afterthe Three Nos agreement uses the Image Restoration concept written by William L. Benoit. Strategies contained in image restoration theory are denial: simple denial and shift the blame, evasion of responbility: provocation, defeasbility, accident, good intensions, reducing offensivnes of event: bolstering, minimization, differentiation, transcendence, attack accuser, compensation, corrective action, and mortification. The research methoed used is a qualitative method with a descriptive approach and uses library research in data collection. Researchers found that the strategy used by South Korea was bolstering by involving EXO CBX and Song Hye Kyo in diplomatic activites with Tiongkok and compensation by using Chinese idols to promote the Hallyu in Tiongkok.